Photographic Memory - Flint, Kate (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractIn this essay, I discuss the relationship between photography, photographic technology, and memory in the final decades of the nineteenth century. I do so first in relation to the desire to possess actual material memories of the deceased, and then move to consider the way in which the photograph was often used as a metaphor for the processes of memory. I argue that apart from exceptional cases, this was, in fact, a false analogy. Taking Amy Levy’s 1888 novel The Romance of a Shop as a text through which to examine both death-bed photography and the workings of memory, I explore the idea of the memory flashing back, suddenly, and link this to the developments that took place in flash photography at the time that Levy was researching her photographically-themed novel. The metaphor of the flash – and the flash-back – has proved of more lasting value in the semantic linking of photography and memory, I argue, than other attempts to link the materiality of the photographic process to the workings of the brain.